2014
DOI: 10.1016/s0140-6736(13)60591-7
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes

Abstract: Over the past decade, knowledge of the pathogenesis and natural history of type 1 diabetes has grown substantially, particularly with regard to disease prediction and heterogeneity, pancreatic pathology, and epidemiology. Technological improvements in insulin pumps and continuous glucose monitors help patients with type 1 diabetes manage the challenge of lifelong insulin administration. Agents that show promise for averting debilitating disease-associated complications have also been identified. However, despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
1,586
3
63

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,100 publications
(1,665 citation statements)
references
References 154 publications
13
1,586
3
63
Order By: Relevance
“…A typical de novo T1D patient presents with hyperglycemia and polyuria, polydipsia and weight loss. Ketoacidosis is common and Ab status at the moment of T1D diagnosis should be verified [21,22,23,24,25,26,27,28,29,30]. …”
Section: Type 1 Diabetesmentioning
confidence: 99%
“…A typical de novo T1D patient presents with hyperglycemia and polyuria, polydipsia and weight loss. Ketoacidosis is common and Ab status at the moment of T1D diagnosis should be verified [21,22,23,24,25,26,27,28,29,30]. …”
Section: Type 1 Diabetesmentioning
confidence: 99%
“…Type 1 diabetes (T1D) results from autoimmune-mediated destruction and dysfunction of insulin-producing pancreatic β cells (1). Prior to the onset of T1D, genetically susceptible individuals develop islet autoantibodies, often during the first few years of life.…”
Section: Introductionmentioning
confidence: 99%
“…In T1D, genetic mutations of human leucocyte antigen (HLA) are the most common variants,3 while also virus infections have been implicated in T1D development 3. The application of genome‐wide association studies (GWAS) has identified over 50 gene variants associated with T2D 2, 4.…”
Section: Introductionmentioning
confidence: 99%